2004
DOI: 10.1007/s00125-004-1408-5
|View full text |Cite
|
Sign up to set email alerts
|

Nelfinavir-induced insulin resistance is associated with impaired plasma membrane recruitment of the PI 3-kinase effectors Akt/PKB and PKC-?

Abstract: Aims/hypothesis. Chronic exposure of 3T3-L1 adipocytes to the HIV protease inhibitor nelfinavir induces insulin resistance, recapitulating key metabolic alterations of adipose tissue in the lipodystrophy syndrome induced by these agents. Our goal was to identify the defect in the insulin signal transduction cascade leading to nelfinavir-induced insulin resistance. Methods. Fully differentiated 3T3-L1 adipocytes were exposed to 30 µmol/l nelfinavir for 18 h, after which the amount, the phosphorylation and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 56 publications
5
53
0
Order By: Relevance
“…Other groups have reported that nelfinavir decreases phosphorylation of Akt at S473 in cancer cell lines, but only after 1 or 3 days of incubation (26,29). In addition, other studies have shown that HIV protease inhibitors can inhibit insulin-stimulated Akt activation (26,38,39). Our study extends these observations by showing that nelfinavir reduces Akt activation in response to EGF or IGF-I, and that decreased Akt stimulation correlates with decreased receptor tyrosine kinase activation.…”
Section: Discussionsupporting
confidence: 83%
“…Other groups have reported that nelfinavir decreases phosphorylation of Akt at S473 in cancer cell lines, but only after 1 or 3 days of incubation (26,29). In addition, other studies have shown that HIV protease inhibitors can inhibit insulin-stimulated Akt activation (26,38,39). Our study extends these observations by showing that nelfinavir reduces Akt activation in response to EGF or IGF-I, and that decreased Akt stimulation correlates with decreased receptor tyrosine kinase activation.…”
Section: Discussionsupporting
confidence: 83%
“…Insulin activates the PI3-K/ Akt signalling, which stimulates glucose transport in adipose and muscle cells (Grinspoon, 2001). Recent studies showed that NFV blocked insulin-induced translocation of Akt to plasma membrane, where PI3-K phosphorylates Akt, resulting in inactivation of Akt (Ben-Romano et al, 2004). It could be the same as NFV inactivates Akt in NSCLC cells.…”
Section: Nfv Induces Growth Arrest and Apoptosis Of Nci-h460 Xenografmentioning
confidence: 99%
“…In this particular study, nelfinavir at 30 µM induced insulin resistance in 3T3-L1 adipocytes by inhibiting recruitment and activation of PI3-K, leading to impaired GLUT4 translocation and thus preventing insulinstimulated glucose uptake. 27,28 These effects were not accompanied by changes in insulin receptor expression or insulin receptor tyrosine phosphorylation. 27 More recently, the effects of nelfinavir were studied in 3T3-L1 adipocytes expressing a GLUT4-green fluorescent protein (GFP) fusion protein to analyse transporter movement.…”
Section: Hpis Impair the Distal Steps In The Insulin Signalling Pathwaymentioning
confidence: 90%
“…27,28 These effects were not accompanied by changes in insulin receptor expression or insulin receptor tyrosine phosphorylation. 27 More recently, the effects of nelfinavir were studied in 3T3-L1 adipocytes expressing a GLUT4-green fluorescent protein (GFP) fusion protein to analyse transporter movement. Fusion of GLUT4 to GFP allows real time visualisation of glucose transporter movement under a fluorescent microscope.…”
Section: Hpis Impair the Distal Steps In The Insulin Signalling Pathwaymentioning
confidence: 90%